Case Report: PNPLA2 Gene Complex Heterozygous Mutation Leading to Neutral Lipid Storage Disease With Myopathy - Shi, Jiejing; Qu, Qianqian; Liu, Haiyan; Zhang, Yan; Cui, Wenhao; Chen, Ping; Lv, Haidong (Frontiers in Integrative Neuroscience, 2021)
Objective: To investigate the clinical features, skeletal muscle imaging, muscle pathology, blood smear and so on of neutral lipid storage disease with myopathy (NLSDM) caused by PNPLA2 gene mutation. Methods: The clinical data, skeletal muscle imaging, pathological data, and genetic test results of a patient with NLSDM treated in our hospital were collected in detail, and the previous literature was reviewed and compared. Results: The main symptoms were muscle weakness and muscular atrophy. Pathological findings of muscle biopsy showed fat deposition in muscle fibers with border cavitation. Fatty droplets were seen in the cytoplasm of neutrophils in peripheral blood. Magnetic resonance imaging of the muscles of both lower extremities showed that muscle in the thigh vastus intermedius, lateral muscles, biceps, and the muscle abdominal area of the middle leg were filled or replaced by fat. Genetic test results suggested mutations in the PNPLA2 gene. Conclusion: NLSDM is a rare clinical myopathy with abnormal lipid metabolism. Characteristic changes can be seen in skeletal muscle imaging and pathology. The detection of PNPLA2 gene mutation is an important basis for diagnosing NLSDM. Asymmetry and progressive limb weakness are the clinical features. Muscle MRI is mainly involved in the posterior group of the lower limbs. Jordans bodies in the peripheral blood smear and a large number of coarse-grained lipid deposits with rimmed vacuoles in muscle fibers are the characteristic pathological changes.